2020
DOI: 10.1111/ijac.13594
|View full text |Cite
|
Sign up to set email alerts
|

New Al2O3–Cu–Ni functionally graded composites manufactured using the centrifugal slip casting

Abstract: The aim of this paper was to establish the general suitability of the centrifugal slip casting technique for fabrication of graded material from the Al 2 O 3-Cu-Ni system. The present investigation is a preliminary one and the obtained results may be regarded as a point for acquiring the new knowledge in the ternary ceramic metal system fabricated using centrifugal slip casting. The rheological study provided the evidence that the suspension used to fabricate composites is a non-Newtonian slurry. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…While a density of 3.83 g/cc was achieved after positioning impregnation + hot pressing at 1700°C, the FGCM fabricated solely by hot pressing at 1800°C had a density of only 3.58 g/cc. Zygmuntowicz et al [24,228] fabricated Al 2 O 3 –Ni and Al 2 O 3 –Cu–Ni FGCMs via centrifugal slip casting process. Aqueous slurries consisting of metal and ceramic powders were first made and centrifuged.…”
Section: Manufacturing Methods Of Fgcmsmentioning
confidence: 99%
“…While a density of 3.83 g/cc was achieved after positioning impregnation + hot pressing at 1700°C, the FGCM fabricated solely by hot pressing at 1800°C had a density of only 3.58 g/cc. Zygmuntowicz et al [24,228] fabricated Al 2 O 3 –Ni and Al 2 O 3 –Cu–Ni FGCMs via centrifugal slip casting process. Aqueous slurries consisting of metal and ceramic powders were first made and centrifuged.…”
Section: Manufacturing Methods Of Fgcmsmentioning
confidence: 99%
“…Previous work on the production of Al 2 O 3 -Cu-Ni composites by the centrifugal casting method showed that in samples containing 15 vol pct metallic phase about 1 pct of the mass of the metal flows out of the specimens after the sintering process. [27] Therefore, it can be concluded that the addition of Mo in three-component composites with Al 2 O 3 matrix is less effective in preventing the outflow of copper during sintering compared to three-component composites with Al 2 O 3 matrix with the addition of Ni particles.…”
Section: A Rheological Analysis Of Slurrymentioning
confidence: 99%
“…[25] The results of our research conducted on composites obtained by slip casting and centrifugal slip casting allowed us to conclude that the addition of the second metallic component, in this case, molybdenum, prevents or limits the escape of liquid copper and may provide better properties of the manufactured composites. [26,27] Thermal analysis and dilatometric research results of the Al 2 O 3 -Cu-Mo composite presented in [28] revealed decomposition and mass were increasing above the temperature of 600°C, which is connected with Cu and Mo oxidation. Higher growth of mass is observed in composites with higher content of the metallic phase.…”
Section: Introductionmentioning
confidence: 97%
“…So far, the CSC method has been mainly used to fabricate pipes from the ceramic-metal system. [6,7] In this study, the method will be adapted to the fabrication of Al 2 O 3 and ZrO 2 -based shapes. Al 2 O 3 and ZrO 2 -based materials play a key role in high-temperature applications.…”
Section: Introductionmentioning
confidence: 99%